A report on the practice-in-industry training in fish preservation - Batioco, Luz G.
Philippine water is rich in natural resources like oysters, edible seaweeds, shells and fishes like tunas, mackerels, and many others which have a great value to every human life as a supplementary food aside from rice. It supplies us calcium, iodine, protein, phosphorous and other minerals taken from the sea foods. This is also the means of livelihood of people living along the coastline. As it is now our natural resources is not fully exploited so that more promises in the near future is expected. Government is making steps to help in exploiting this supply in scientific manner by establishing fishery schools in the Philippines and colleges in which students are taught more on the line of their specialization so that, after graduation they may help our fisherfolks the right way of catching, culturing and preserving the catch for a definite period of time. Government agency like the Emergency Employment Agency is establishing cannery and cod storage on places where fishing industry is the major industry. In one way or another, this project, helps us to conserve our dollar reserves now beginning to diminish.